A Multi-criteria Decision Model for Construction Material Supplier Selection. (2017) - Cengiz, A.E.; Aytekin, O.; Ozdemir, I.; Kusan, H.; Cabuk, A.
Abstract: Supply chain management (SCM) is a sophisticated concept which contains all material-related activities of construction projects. In the last decade, construction supply chain management (CSCM) has become a new challenge for construction managers in order to procure right quantities of materials to construction site on time, and within the pre-defined budget. Supplier selection as a significant process in SCM is a multi-criteria decision making problem. There is a broad literature on supplier selection that examines selection of supplier evaluation criteria and multi-criteria decision making methods. Individual and integrated multi-criteria decision approaches are studied by many researchers. In this paper, supplier selection analysis for wall, cladding and roofing construction materials are researched. Whilst literature review and expert panel are employed in order to identify criteria, weights of each criterion are determined by an extensive questionnaire survey. Participants are selected from the experts in construction industry, universities and governmental institutions. Analytic Network Process (ANP) is utilized as multi-criteria decision making methodology and weights of criteria are obtained. This study is a section of an on-going doctoral research, in other words, a part of a more comprehensive model. The study is significant due to the development of a new approach on construction material supplier selection and the basis of the model that is able to provide decision support for construction project participants throughout the project life cycle.